2020
DOI: 10.1016/j.omto.2020.10.006
|View full text |Cite
|
Sign up to set email alerts
|

Retargeted and Multi-cytokine-Armed Herpes Virus Is a Potent Cancer Endovaccine for Local and Systemic Anti-tumor Treatment

Abstract: Oncolytic viruses (OVs) are novel anti-tumor agents with the ability to selectively infect and kill tumor cells while sparing normal tissue. Beyond tumor cytolysis, OVs are capable of priming an anti-tumor immune response via lysis and cross-presentation of locally expressed endogenous tumor antigens, acting as an “endovaccine.” The effectiveness of OVs, similar to other immunotherapies, can be hampered by an immunosuppressive tumor microenvironment. In this study, we modified a previously generated oncolytic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
51
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 23 publications
(55 citation statements)
references
References 43 publications
3
51
1
Order By: Relevance
“…An emerging approach to maximize the efficacy of oncolytic viruses involves arming them with payloads to enhance antitumor immunity [ 1 ]. We and others recently demonstrated that interleukin 12 (IL12) significantly enhanced the antitumor efficacy of a retargeted oncolytic virus through T cell activation [ 23 , 66 ]. Based on these evidences, we devised an arming strategy to insert IL12 into the intergenic site between viral US1 and US2 genes of THV_SS1 ( Figure 2 c) as preparatory for preclinical translation.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…An emerging approach to maximize the efficacy of oncolytic viruses involves arming them with payloads to enhance antitumor immunity [ 1 ]. We and others recently demonstrated that interleukin 12 (IL12) significantly enhanced the antitumor efficacy of a retargeted oncolytic virus through T cell activation [ 23 , 66 ]. Based on these evidences, we devised an arming strategy to insert IL12 into the intergenic site between viral US1 and US2 genes of THV_SS1 ( Figure 2 c) as preparatory for preclinical translation.…”
Section: Resultsmentioning
confidence: 99%
“…The use of viral vectors for gene therapy, vaccine delivery, and oncolytic viruses is now a reality, with thousands of clinical trials completed, ongoing, or approved worldwide [ 1 , 3 , 82 , 83 ]. Oncovirotherapy with retargeted viruses is revealing a promising potential for the treatment of many cancer indicators, including breast cancer [ 7 , 23 , 47 , 66 , 84 ]. We recently characterized preclinical models of HER2-positive tumors in the framework of combination with checkpoint inhibitors [ 7 , 23 , 47 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations